The impact of social media on intellectual property law - Fatin Hamamah; Munaji Munaji; Erna Erna; Sukama Sukama; Marhendi Marhendi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
In the digital era, social media has revolutionized the way we communicate and interact, having a significant impact on intellectual property (IP) law. Social media platforms such as Facebook, Twitter, Instagram, and TikTok have blurred the lines between private and public spaces, creating new challenges in implementing and enforcing IP laws. This research aims to explore various legal strategies the importance of legal awareness education among social media users, and the role of technology in supporting intellectual property law enforcement. The research method used is a normative research method to investigate the impact of social media on intellectual property law. The results of the analysis show that social media influences the perception and application of IP law, including issues of privacy and the management of personal and social boundaries. A deep understanding of the dynamics of social media and IP law is critical to ensuring copyright and intellectual property protection in an increasingly connected world. The importance of intellectual property law in the digital era lies not only in the protection of copyrights and patents but also in the adaptation and evolution of the law to address new challenges arising from technological developments. Intellectual property law in today's digital era cannot be ignored. In the digital era that continues to develop, technology has become the main factor influencing change in society, including in the legal aspect.Keywords: Social Media, Copyright, Intellectual Property.